Optimum Design and Test of a Novel Bionic Electronic Stethoscope based on the Cruciform Microcantilever with Leaf Microelectromechanical Systems Structure. Issue 11 (19th March 2022) - Zang, Junbin; Zhou, Chenzheng; Xiang, Menghui; Wang, Juliang; Wang, Haoxin; Zhang, Zhidong; Xue, Chenyang
Abstract: This paper proposes a heart sound sensing structure and system by combining the traditional auscultation structure and human‐like ear eardrum gas–solid coupling sound conduction process. This system is based on the lever pickup mechanism of eardrum vibration and the traditional stethoscope pickup amplification, microelectromechanical system (MEMS) technology, and the detection principle of piezoresistive and Wheatstone bridge. The optimal size and process parameters of the biomimetic sensor structure are given through theoretical calculation and numerical simulation on Comsol and SRIM. Computer numerical control, 3D printing, MEMS technology, and 3D heterogeneous integration technology are used to complete the precise processing and encapsulation of the proposed structure. After the performance tests, results show that the optimal structure can collect directional signals, with a bandwidth from 10 Hz to 1 kHz, which can effectively cover the range of the heart frequency. The signal‐to‐noise ratio is improved by 2.3 dB compared with the 3M stethoscope. An electrocardiogram and phonocardiogram synchronization detection system is developed with this structure. The structure and system can be effectively applied to the high‐quality collection and intelligent recognition of heart sound data sets. The recognition accuracy can reach 98.5%. It is highly effective for early screening and intelligent diagnosis of cardiovascular diseases. Abstract : This paper proposes a heart sound sensing structure and system by combining the traditional auscultation structure and human‐like ear eardrum gas–solid coupling sound conduction process. The test result shows that the structure and system are stable and reliable and can be effectively applied to the high‐quality collection and intelligent recognition of heart sound data sets.